2008
DOI: 10.1111/j.1600-0609.2008.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of DKK‐1 decrease in patients with multiple myeloma responding to anti‐myeloma treatment

Abstract: Lytic bone disease is one of the major clinical problems in multiple myeloma (MM) patients and has negative impact both on overall survival and quality of life (1, 2). Myeloma bone disease is characterized by a dysbalance in bone remodeling, caused by enhanced osteoclast activity and decreased bone formation (3,4). In animal models a mutual stimulation has been found between myeloma bone disease and tumor progression (5, 6). Furthermore, the bone marker carboxy-terminal telopeptide of type I-collagen (ICTP) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…33 The serum concentration of DKK1 has been also shown to decrease with response to therapy. 34 Such association with DKK1 and bone disease has also been established in other malignancies including breast, esophageal, lung, prostate, and colon cancers, 12,13,[15][16][17][18] making DKK1 an important target to improve bone disease in cancer in general and myeloma in particularly, where suppression of OB function is perhaps the greatest. Figure 4.…”
Section: Discussionmentioning
confidence: 93%
“…33 The serum concentration of DKK1 has been also shown to decrease with response to therapy. 34 Such association with DKK1 and bone disease has also been established in other malignancies including breast, esophageal, lung, prostate, and colon cancers, 12,13,[15][16][17][18] making DKK1 an important target to improve bone disease in cancer in general and myeloma in particularly, where suppression of OB function is perhaps the greatest. Figure 4.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, high levels of DKK1 in patients' serum are associated with poor prognosis in various cancers including oesophageal squamous cell carcinoma [136] , lung cancer [137] , breast cancer [138] and cervical cancer [138] , suggesting that the serum level of DKK1 may also reflect the prognosis of HCC patients. In multiple myeloma, high DKK1 serum levels are associated with osteolytic bone lesions [139] and patients responding to anti-myeloma treatment show a decrease in DKK1 serum levels [140] , suggesting the involvement of DKK1 in this aspect. Recently, Fulciniti et al [141] evaluated the effect of anti-DKK1 monoclonal antibody (BHQ880) in a multiple myeloma mouse model and found that it induced bone formation and inhibited tumour-induced osteolytic bone lesions.…”
Section: Dkk1mentioning
confidence: 99%
“…Furthermore, serum DKK-1 correlated with the number of bone lesions [45]. In a recent study, DKK-1 serum levels were examined in MM patients receiving different treatment regimens, also including novel agents [46]. Serum DKK-1 decreased in myeloma patients responding to therapy, irrespective of the regimen chosen, but not in nonresponders.…”
Section: Myeloma Cells Suppress Osteoblast Differentiation and Functionmentioning
confidence: 99%